Ireland : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
The performance of the Irish economy has been impressive. The outlook is broadly favorable, but there are risks to achieving a smooth transition to a sustainable rate of growth. The government's reform of the tax structure is commendable. To sustain high growth over the medium term, Ireland must address challenges with regard to wage determination, increasing competition, and strengthening the medium-term basis of fiscal policy. Strengthening competition through privatization and regulatory reform are key to securing a high rate of sustainable growth in the medium term.